Implementation of E-PACE Mobile in Improving the Quality of Non-Business Licensing Services in West Papua Province - Yakobus Richard Murafer; Terianus Luther Safkaur; Eduard Metusala Johanis Kocu; Jackson Yumame; Melpayanty Sinaga (FOUNDAE (Foundation of Advanced Education), 2026)
Digital transformation has become central to improving public service quality, yet evidence on how mobile government applications perform in remote and infrastructure-constrained regions remains limited. This study evaluates the implementation of E-PACE Mobile, a front-end application integrated with the SiCANTIK Cloud ecosystem, at the West Papua Province Investment and One-Stop Integrated Service Agency (DPMPTSP), and assesses its contribution to improving the quality of non-business licensing services in line with SDG 16. A single embedded qualitative case study design was employed, with four sub-units of analysis (application features, institutional framework, infrastructure, and users), supported by document analysis as the primary data collection technique. Primary textual data were obtained from institutional documents of the DPMPTSP, evaluation reports of the Indonesian Ombudsman (2022–2025), documentation of the E-PACE Mobile system, and official statistical data of the BPS, and analyzed using a hybrid deductive–inductive thematic approach framed by the E-GovQual dimensions and the Technology–Organisation–Environment (TOE) framework. The findings indicate that E-PACE Mobile enhances service efficiency through its Digital Approval feature and strengthens transparency via cryptography-based QR code permit verification. However, service reliability is constrained by rural internet access, which stands at only 55.75%. Citizen support remains the weakest dimension due to the absence of an integrated helpdesk, and the organisational capacity paradox (strong political commitment coupled with technical staff limitations) restricts scalability. This study makes three theoretical contributions: (1) the addition of territorial logistical efficiency as a new E-GovQual metric relevant to island and mountainous regions, (2) the proposal of a cultural sub-dimension within the TOE Environment component, and (3) the formalisation of the organisational capacity paradox as a structural pattern of e-government in Indonesia’s 3T regions. In practical terms, the expansion of E-PACE Mobile should be approached sequentially, beginning with the reinforcement of 4G telecommunications infrastructure in districts classified as 'red zones', followed by the integration of WhatsApp/SMS-based help desks and community-based digital ambassador programmes. This approach will ensure that the implementation of E-PACE Mobile does not exacerbate existing service inequalities.